Barebacking in France: From controversy to community ownership? An account of the 'Zone NoKpote' workshops conducted by AIDES in 2009. (February 2015) - Castro, Daniela Rojas; Girard, Gabriel
Research on bareback behaviours and identities constitutes a wide field of academic work. Literature on this issue has focused on the associated psycho-sociological factors, on the evolution of gay sociabilities and on the discursive and socio-political uses of bareback sex. But few of these studies have explored local appropriation of the terms in non-English-speaking contexts. The present article aims to provide an empirical illustration of this process in the French context. It is based on a qualitative study of the impact of a series of sexual health workshops for men who do not use condoms ('barebackers').